تطور قطاع التأمين في الجزائر - بالي, مصعب; صديقي, مسعود (جامعة الوادي University of Eloued, 2016)
مر سوق التأمين الجزائري بعدة مراحل لا يمكن التغاضي عن أي مرحلة منها, وهذا لتأثير ومساهمة كل منها فيما وصل إليه الآن, بدءا بالحقبة الاستعمارية مرورا بمرحلة الاستقلال وما شهده هذا السوق من احتكار الدولة للنشاط, وصولا للانفتاح والتحرير الكلي في ظل تحول الاقتصاد الجزائري إلى اقتصاد السوق. شهدت صناعة التأمين تغيرا هيكليا خلال السنوات الأخيرة، تزامن مع رفع احتكار الدولة عن هذا القطاع وانفتاحه على المنافسة. ساهم هذا التغير في تطور القطاع من حيث معدلات النمو المرتفعة ودخول شركات تأمين جديدة، بالإضافة إلى تنوع القوانين والتشريعات والهيئات التي أصدرتها وأنشأتها الدولة لتنظيم ومراقبة هذا القطاع. Assurance market underwent many stages that cannot be avoided. All that was due to the impact of each stage on the current situation of assurance market: starting with the colonial period, then the State monopoly of this activity during the independence period, till the total openness of this market during the move of the Algerian economy to market economy. Assurance industry witnessed an infrastructural change during the last years. This was in parallel with the state openness of this sector to competition. The change was represented in the development witnessed by this sector across increased development rates and the entrance of new assurance companies in addition to the diversification of laws, legislations and institutions established by the state in order to organize this sector.
The development of the insurance sector in Algeria
مقال- مجلة رؤى اقتصادية
Keywords: التأمين، قطاع التأمين الجزائري، شركات التأمين, هيئات الرقابة: Insurance, Algerian insurance sector, Insurance companies, Oversight bodies